Implementasi kebijakan penurunan stunting di kabupaten Donggala - Dalili, La Samudia; Daswati, Daswati; Chaeriah Ahsan, Sitti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The research aims to describe the implementation of the Stunting Reduction Policy in Donggala Regency; the study uses a qualitative descriptive approach; informants are determined through purposive sampling; data collection includes observation, interviews, and documentation; data analysis follows an interactive model consisting of data condensation, data presentation, and conclusion drawing. The research findings are as follows: The policy goals and targets are clear, easy to understand, and measurable. This is evident from Presidential Regulation No. 72 of 2021 concerning the Acceleration of Stunting Reduction, Chapter II, Articles 4 and 5, which states that the National Strategy for the Acceleration of Stunting Reduction aims to achieve the sustainable development goals by 2030 through the national target of 14% stunting prevalence by 2024. The implementer resources are adequately sufficient. Competent human resources (HR) of TPPS are in place to implement the Presidential Regulation No. 72 of 2021 according to their respective duties. Communication between organizations is functioning well. Coordination activities by TPPS, through meetings and gatherings, cover all aspects related to Presidential Regulation No. 72 of 2021. The attitude of the implementers, namely TPPS, has been responsive and proactive towards Presidential Regulation No. 72 of 2021 to achieve the stunting prevalence target of 14% by 2024. The social, economic, and political environment is conducive. There is support from the community, policy target groups, members, and prospective members of the legislature (DPR, DPR candidates, and DPD) for Presidential Regulation No. 72 of 2021 concerning the Acceleration of Stunting Reduction. It is hoped that the Regent of Donggala will oversee all TPPS activities to ensure that the stunting budget is appropriately allocated; it is also expected that TPPS will draft written Standard Operating Procedures (SOPs) to serve as guidelines in the implementation of tasks related to the policy implementation of Presidential Regulation No. 72 of 2021 concerning the Acceleration of Stunting Reduction to ensure the effective execution of Convergence Action activities.